1996
DOI: 10.1093/rheumatology/35.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Amyloidosis in Patients With Rheumatoid Arthritis: Diagnostic and Prognostic Value of Gastroduodenal Biopsy

Abstract: Upper gastrointestinal endoscopy was performed in patients with rheumatoid arthritis (RA) during the period 1989-1991, and biopsy specimens were obtained from the stomach and from the duodenum for examining amyloid deposits. Among 407 patients, gastrointestinal amyloidosis was confirmed in 54 (13.3%). Twenty-two patients were regarded as having slight amyloid deposits, while 32 patients were categorized as having marked amyloid deposits. The incidence of clinical manifestations suggestive of systemic amyloidos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
73
0
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 22 publications
4
73
0
4
Order By: Relevance
“…This rate is almost the same as that shown in the previous biopsy studies (1,15,16). These results suggest that abdominal fat aspiration biopsy with phenol Congo red staining is sufficiently sensitive and useful in the diagnosis of systemic reactive AAamyloidosis secondary to RAeven before the appearance of clinical symptoms.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This rate is almost the same as that shown in the previous biopsy studies (1,15,16). These results suggest that abdominal fat aspiration biopsy with phenol Congo red staining is sufficiently sensitive and useful in the diagnosis of systemic reactive AAamyloidosis secondary to RAeven before the appearance of clinical symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…In the histopathological diagnosis of reactive AA amyloidosis either the gastroduodenal and rectal mucosa or abdominal fat tissue has been commonly used as a biopsy site (1,(12)(13)(14)(15)(16)(17)(18). A few reports have shown that the bulbus and the second portion of the duodenumare the most sensitive site for biopsy (15,16), but an endoscopic examination is often difficult and risky in RApatients, particularly in those with either various complications, including ischemic heart disease, or involvement of the cervical spine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary amyloidosis, one of the most common forms of clinically important systemic amyloidosis, is a result of chronic inflammatory diseases such as rheumatoid arthritis (1)(2)(3) and chronic infections such as malaria, tuberculosis, and leprosy (4)(5)(6). Amyloid protein A (AA) is the amyloid fibril protein deposited in secondary, or AA, amyloidosis.…”
mentioning
confidence: 99%
“…Prolonged elevation of SAA is the major inciting factor for AA amyloidosis developing in chronic inflammatory diseases. The extensive and persistent production of SAA under chronic active inflammatory conditions is the critical prerequisite for AA amyloidosis fibrillogenesis, and approximately 10-15% of Japanese RA patients have AA amyloidosis deposits in their gastroduodenal mucosa as shown by endoscopic biopsy (Kobayashi et al, 1996). SAA is genetically polymorphic with four loci (SAA1, SAA2, SAA3, and SAA4) located on chromosome 11 (Yamada, 1999).…”
mentioning
confidence: 99%